"Bonds" or "Calvin Klein" Down-under: Consumer ethnocentric and brand country origin effects towards men's underwear - Lee, W.; Phau, Ian; Roy, Rajat (Emerald Group Publishing Limited, 2013)
Purpose: The purpose of this paper is to determine if high versus low ethnocentric consumers differ in their attitudes toward buying domestic and foreign brands of underwear that are made domestically or in foreign countries. Design/methodology/approach: Australian residents recruited through a mall intercept participated in this study through a self-completed questionnaire. Fishbein’s Multi-Attribute model was used as the measure, along with repeated-measures ANOVA and t-tests, to examine whether the groups differed in their attitudes toward buying underwear with “Made in Australia”, “Made in the USA”, and “Made in China” labels. Findings: The findings generally indicated that there is no significant difference between high and low ethnocentric consumers in attitude towards underwear that are made in Australia and the USA. On the other hand, high ethnocentric consumers viewed domestically made and branded underwear as more durable, easier to care for, better priced, more colourful, more attractive, more fashionable, of stronger brand name, more appropriate for occasions, and more choices of styles. Domestically-made but foreign-branded underwear is viewed as easier to care for and better priced. Practical implications: The study suggests that China should improve its country image as compared to such developed nations as Australia and the USA in terms of production and manufacturing standards. The study also purports that American underwear brands with strong presence in the global fashion world that have not already established operation in Australia can consider entering the market.Originality/value: The paper fills the gap in the ethnocentrism literature by validating the study in Australia and focusing on the attitudes of high ethnocentric (and low ethnocentric) consumers. It also examines underwear, which is a common product category in apparels but inherently deficient in the literature.